(3eKdKGJ bWQHs - (3bWQH , eMeO Hf GdeSJfjQ Hf CMeO, CHh Ydj,J (B206 (3g` s
(3ChdgG (B:s
(3GdnZeQ hGdpZeQ hGdoZeQ s
(3BNQgG (B:s
(3GdnbQi hGdpbQi hGdobQi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B95 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B15s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GddZIs